A Criminological Study Of Cybercrime For The Crime Of Defamation - Ali Yusran Gea; Nur Muniifah; Muhammad Yasin Ali Gea (SEAN Institute, 2024)
This research aims to determine the criminological study of Cybercrime for criminal acts of defamation through a criminological study approach, namely through the perspective of the perpetrator of the crime. This research uses a normative approach to secondary data which is then analyzed descriptively-analytically. Based on the research, it was concluded that in a criminological study of cybercrime, the criminal act of defamation from the perspective of the perpetrator committed the criminal act of defamation because the perpetrator felt hurt by the actions that had been carried out by the victim so that the perpetrator took retaliation by defaming the victim through cyberspace. (social media).